2014
DOI: 10.1186/1471-2458-14-206
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and severity of early childhood caries in Southern Italy: a preschool-based cross-sectional study

Abstract: BackgroundThis survey was intended to investigate prevalence and severity of early childhood caries (ECC) in a sample of children in Southern Italy and to identify factors that may be related to this condition.MethodsThe study was designed as a cross-sectional survey. The study population (children aged 36–71 months) attending thirteen kindergartens was randomly selected through a two-stage cluster sampling procedure. Parents/guardians of all eligible children were invited to participate filling out a structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
87
7
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(113 citation statements)
references
References 40 publications
14
87
7
5
Order By: Relevance
“…We found that baby bottle use did not increase ECC incidence (p=0.56). In addition to our group, Nobile et al [18] also reported that baby bottle use did not increase ECC prevalance. American Academy of Pediatric Dentistry (AAPD) recommends that baby bottle should be used at an early age from-first twelve month's of age and then children between 12-18 months should be made accustomed to using cup and finally children older than 18 months should only use cup [1].…”
Section: Discussionsupporting
confidence: 69%
“…We found that baby bottle use did not increase ECC incidence (p=0.56). In addition to our group, Nobile et al [18] also reported that baby bottle use did not increase ECC prevalance. American Academy of Pediatric Dentistry (AAPD) recommends that baby bottle should be used at an early age from-first twelve month's of age and then children between 12-18 months should be made accustomed to using cup and finally children older than 18 months should only use cup [1].…”
Section: Discussionsupporting
confidence: 69%
“…Other studies demonstrating the association between breastfeeding over 18 months and increased caries risk did not adjust for confounders [Yonezu et al, 2006;Prakasha Shrutha et al, 2013;Nobile et al, 2014]. Our analysis, adjusted for confounders, did not observe an association between prolonged full or any breastfeeding for >12 months and increased caries risk ( tables 4 , 5 ).…”
Section: Discussioncontrasting
confidence: 51%
“…An increased risk of dental caries associated with prolonged breastfeeding has been reported in several studies [Yonezu et al, 2006;Saraiva et al, 2007;Feldens et al, 2012;Prakasha Shrutha et al, 2013;Chaffee et al, 2014;Hong et al, 2014a;Nobile et al, 2014;Jain et al, 2015;Kato et al, 2015]. Compared to cow's milk, human milk presents more cariogenic properties responsible for dental caries, because it contains more carbohydrates but less calcium, phosphorus, and protein [Erickson and Mazhari, 1999;Bowen and Lawrence, 2005].…”
mentioning
confidence: 99%
“…Previous studies had found that the level of education of caregivers, especially mothers, was notably associated with undertaking preventive measures in children (44)(45)(46). In our study, the education of caregivers was relatively high: 63% of participants had university degree and the others were high school graduates.…”
Section: Acta Facultatis Medicaementioning
confidence: 52%